Die Ruine Godesberg bey Bonn - Bodmer, Rudolph, 1805-1841 (engraver):::Creator::::::::::::; Lasinsky, Adolf, 1808-1871 (artist):::Contributor:::::::::::: (Coblenz; Fr. Röhling)
Engraving of the ruins of Godesberg near Bonn by Rudolph Bodmer based on drawing by Adolf Lasinsky,